(untitled) (Baghdad Science Journal, 2025)
This work comprises the synthesis of new thioxanthone derivatives containing C-substituted thioxanthone. To obtain these derivatives, the o-mercapto benzoic acid was chosen as the starting material, which was reacted with dry benzene in sulfuric acid (98 %) to produce the thioxanthone (1). The 2,7-(disulfonyl phosphine imine) thioxanthone (4-8) were prepared from reaction of compound (1) with chlorosulfonic acid gave 2,7-(disulfonyl chloride) thioxanthone (2). Treatment of (2) with sodium azide to produce 2,7-(disulfonyl azide) thioxanthone (3). Condensation of (3) with phosphorus compounds afforded compounds (4-8). The 2,7-(disulfonamide) thioxanthone (9-21) was obtained when compound (2) condensed with different aromatic amines, it gave the expected amides (9-21).